Prostate-specific antigen kinetics parameters are predictive of positron emission tomography features worsening in patients with biochemical relapse after prostate cancer treatment with radical intent: Results from a longitudinal cohort study. (June 2014) - Gacci, Mauro; Cai, Tommaso; Siena, Giampaolo; Minervini, Andrea; Torshizi, Mozhgan Fayaz; Bartolini, Matteo; Giannì, Gianluca; Saieva, Calogero; Ceroti, Mauro; Detti, Beatrice; Livi, Lorenzo; Pupi, Alberto; et al.
Abstract Objective. The aim of this study was to identify prostate-specific antigen (PSA) kinetics parameters predictive of [18F]fluorocholine positron emission tomography/computed tomography (18FC PET/CT) features worsening in a cohort of patients with biochemical failure after prostate cancer treatment. Material and methods. This longitudinal cohort study comprised 103 consecutive patients. All patients underwent two 18FC PET/CT scans: one at baseline (PET1) and one after 6 months (PET2). Total PSA (tPSA), PSA velocity (vPSA), PSA doubling time (PSAdt), absolute variation in PSA values between PET2 and PET1 (ΔPSA), and percentage variation in PSA between the two PSA measurements (PSA%) were measured in each patient. Progression of disease on 18FC PET/CT findings was compared with the PSA kinetics parameters. The major outcome measure was disease progression at PET2. Results.18FC PET/CT progression between PET1 and PET2 was reported in 64 patients (62.1%), while in 39 cases it remained unvaried. The following PSA kinetic parameters correlated with worsened 18FC PET/CT findings: ΔPSA >5 ng/ml [odds ratio (OR = 6.44, 95% confidence interval (CI) 1.04–39.6; p = 0.04], vPSA >6 ng/ml/month (OR = 5.2, 95% CI 0.9–29.8; p = 0.05) and PSAdt <6 months (OR = 5.2, 95% CI 0.4–5.4; p = 0.03). From receiver operating characteristics (ROC) analysis, the combination with the three PSA kinetics parameters for predicting worsened 18FC PET/CT findings resulted in a sensitivity of 86% (95% CI 77–92%) and specificity of 77% (95% CI 65–85%). Conclusion. PSA kinetics is strictly related to 18FC PET/CT findings. In patients with biochemical relapse, ΔPSA >5 ng/ml, PSAdt <6 months and vPSA >6 ng/ml/month are highly predictive of 18FC PET/CT features worsening, independently from the treatment received.